Olanzapine-induced hypertriglyceridemia in cancer care: A silent metabolic risk - Bilal Kazi; Imaan Rumani; Marzooka Nazim Chishti Kazi; Prashant Manohar Gaikwad (Current Problems in Cancer: Case Reports)
Olanzapine (Zyprexa), an atypical antipsychotic, is used off-label for managing nausea in advanced cancer patients but is linked to severe metabolic side effects, including hypertriglyceridemia. This case involves a metastatic gastric carcinoma patient with no known metabolic disorder who developed critically elevated triglycerides (2898 mg/dL) after starting olanzapine for nausea. Her lipid levels significantly improved with medical management, allowing her to proceed for apheresis for the planned CAR-T treatment. This case underscores the need for vigilant metabolic monitoring in patients on Olanzapine (Zyprexa), even those without known risk factors, to prevent serious complications.